Copper-Catalyzed C–H Stereoselective Cyanation of Alkenes by Using an α-Iminonitrile as a Cyanating Reagent - Chen, Zhen-Bang; Gao, Qing-Qing; Liu, Kui; Zhu, Yong-Ming (Synlett, 2019)
The first copper-catalyzed cyanation through alkene C–H bond activation by using an α-iminonitrile as a cyanating agent has been realized. The approach efficiently constructs acrylonitriles in good yields with the advantages of high regioselectivity, cost-benefit, and operational simplicity.
Keywords: copper catalysis; C–H activation; cyanation; iminonitriles; alkenes; acrylonitriles